Analisis Content Creator, Social Media Engagement, Customer Trust Terhadap Loyalitas Pelanggan Daviena Skincare di Jawa Tengah - Santang, Nyimas Ayu Rara; Farida, Ida; Putra, Febrianur Ibnu Fitroh Sukono; Setiawan, Aries (Jurnal Ekonomi dan Bisnis, 2026)
This research is driven by the intense competition within the beauty industry and the emergence of negative issues regarding alleged "overclaiming" practices by Daviena Skincare products. The primary focus of this study is to analyze how customer loyalty is formed and maintained despite issues that potentially undermine consumer confidence. This study employs a quantitative research method with a positivism approach, utilizing multiple linear regression analysis via SPSS 25. The research population consists of Daviena Skincare consumers residing in Central Java. Samples were selected using a purposive sampling technique, specifically targeting consumers who have used the products more than twice. Based on the Hair formula, a total of 110 respondents were obtained. The objective of this research is to identify and analyze the influence of content creators, social media engagement, and customer trust on Daviena Skincare’s customer loyalty in Central Java, particularly in the aftermath of the overclaim issue. Data were collected through questionnaires using a Likert Scale, followed by data quality testing (validity and reliability), classical assumption tests, and multiple linear regression modeling. The findings indicate that the content creator variable is in the "very high" category (4.24), while social media engagement (3.86) and customer trust (3.93) are in the "high" category. Overall, these three factors play a crucial role in shaping Daviena Skincare's customer loyalty, which remains in the "very high" category (4.23). Despite the overclaim controversy, the practical implications of this research suggest that brands in the beauty industry must remain transparent, responsive, and maintain positive communication with consumers to sustain loyalty even when facing negative issues. Penelitian ini dilatarbelakangi oleh persaingan ketat di indstri kecantikan dan adanya isu negative berupa dugaan praktik overclaim pada produk Daviena Skincare. Fokus utama penelitian adalah menganalisis bagaimana loyalitas pelanggan tetap terbentuk dan terjaga meskipun terdapat isu yang berpotensi mempengaruhi kepercayaan konsumen. Metode Penelitian kuantitatif dengan pendekatan positivisme, menggunakan Analisis data regresi linier berganda melalui alat bantu SPSS 25. Populasi penelitian merupakan konsumen Daviena Skincare yang bertempat tinggal di Jawa Tengah dan mengambil sampel menggunakan teknik purposive sampling dengan kriteria yang telah menggunakan produk lebih dari 2 kali.berdasarkan rumus Hair, diperoleh jumlah responden sebanyak 110 orang. Tujuan riset ini untuk mengetahui dan menganalisis pengaruh content creator,social media engagement, dan customer trust terhadap loyalitas pelanggan Daviena Skincare di Jawa Tengah, Khususnya pasca dampak isu Overclaim. Data dikumpulkan melalui penyebaran kuesioner dengan Skala Likertmeliputi uji kualitas data (validitas dan reliabilitas), uji asumsi klasik, serta uji model regresi linier berganda. Temuan menunjukkan bahwa variable content creator berada pada kategori sangan tinggi (4,24), sementara social media engagement (3,86) dan customer trust (3,93) berada pada kategori tinggi. Secara keseluruhan, ketiga faktor tersebut berperan penting dalam membentuk loyalitas pelanggan Daviena Skincare yang tetap berada pada kategori sangat tinggi (4,23) meskipun ditengah isu overclaim.